UNPLUGGED CITY Escaping from Global Networks and Flows Trap? New Geographies of Logistics - Gonzalo Cantos Mateos (European Regional Science Association (ERSA), 2011)
The urban and regional influence of contemporary passengers, goods and information traffic within the new global economy based on knowledge and logistics, and the physical structures that shape the networks (harbours, airports, train stations, motorways) are assumed as capitally important. Nevertheless, so far, the impact of these dynamics is much more attached to hierarchical processes of socio-spatial fragmentation-segmentation-polarization rather than balanced re-distributive systems. Global connectivity has as much strengths as threats, and the integration within the new production, consumption and distribution geographies generates as much opportunities as irreversible mutations. Unplugged City is presented as an incursion on connectivity and accessibility, exploring the strengths and threats derived from the management of logistics and freight transport flows within the frame of the so-called "catch-up" economy. The Trans-European Transport Network Plan (TEN-T) will be on focus as the main policy-making framework behind the new geographical transformation in Europe. The importance of the exponential growing freight transport and logistic sector has been exposed as a key factor to understand the bases of current globalisation. The sharp changes generated by the dropping of transport cost in patterns of production-consumption-distribution geographies have to be contrasted with deep transformations of labour market, linkages between transport and industrial location and new network models. What is close is just what is cheap. Distances nowadays are no measured in kilometres or hours but in Euros, imposing a new logic for the global geographic structure. Regions with better access to locations of input materials and markets are assumed to be more productive, more competitive and hence more successful than more peripheral and isolated regions. But this hypothesis has to be urgently reformulated, contrasting transport policies with quantitative research and the appraisal of real socio-economic impact of the new transport geographies. The assumed idea of connectivity as pure benefiting will be critically discussed as a much complex phenomena. Corridors are fostering the survival of core regional centres meanwhile a growing regional imbalance is monitored; regions that still have to deal with environmental, budgetary and indirect issues derived from the management of these flows.
Keywords: 330